Global Gene Knockout of Kcnip3 Enhances Pain Sensitivity and Exacerbates Negative Emotions in Rats - Guo, Yu-Peng; Zhi, Yu-Ru; Liu, Ting-Ting; Wang, Yun; Zhang, Ying (Frontiers in Molecular Neuroscience, 2019)
The Ca2+-binding protein Kv channel interacting protein 3 (KChIP3) or downstream regulatory element antagonist modulator (DREAM), a member of the neuronal calcium sensor (NCS) family, shows remarkable multifunctional properties. It acts as a transcriptional repressor in the nucleus and a modulator of ion channels or receptors, such as Kv4, NMDA receptors and TRPV1 receptors on the cytomembrane. Previous studies of Kcnip3-/- mice indicated that KChIP3 facilitates pain hypersensitivity by repressing Pdyn expression in the spinal cord. Conversely, studies from transgenic daDREAM (dominant active DREAM) mice indicated that KChIP3 contributes to analgesia by repressing Bdnf expression and attenuating the development of central sensitization. To further determine the role of KChIP3 in pain transmission and its possible involvement in emotional processing, we assessed the pain sensitivity and negative emotional behaviors of Kcnip3-/- rats. The knockout rats showed higher pain sensitivity compared to the wild-type rats both in the acute nociceptive pain model and in the late phase (i.e., 2 d, 4 d and 6 d post complete Freund’s adjuvant injection) of the chronic inflammatory pain model. Importantly, Kcnip3-/- rats displayed stronger aversion to the pain-associated compartment, higher anxiety level and aggravated depression-like behavior. Furthermore, RNA-Seq transcriptional profiling of the forebrain cortex were compared between wild-type and Kcnip3-/- rats. Among the 68 upregulated genes, 19 genes (including Nr4a2, Ret, Cplx3, Rgs9, and Itgad) are associated with neural development or synaptic transmission, particularly dopamine neurotransmission. Among the 79 downregulated genes, 16 genes (including Col3a1, Itm2a, Pcdhb3, Pcdhb22, Pcdhb20, Ddc, and Sncaip) are associated with neural development or dopaminergic transmission. Transcriptional upregulation of Nr4a2, Ret, Cplx3 and Rgs9, and downregulation of Col3a1, Itm2a, Pcdhb3 and Ddc, were validated by qPCR analysis. In summary, our studies showed that Kcnip3-/- rats displayed higher pain sensitivity and stronger negative emotions, suggesting an involvement of KChIP3 in negative emotions and possible role in central nociceptive processing.